HILDA+ version 2.0: Global Land Use Change between 1960 and 2020 - Karina Winkler; Richard Fuchs; Mark D A Rounsevell; Martin Herold (PANGAEA, 2025)
HILDA+ version 2.0 is an updated version of the HILDA+ (HIstoric Land Dynamics Assessment+) doi:10.1594/PANGAEA.921846. It is a global dataset on annual land use/cover change between 1960-2020 at 1 km spatial resolution. It is based on a data-driven reconstruction approach and integrates multiple open data streams (from high-resolution remote sensing, long-term land use reconstructions and statistics). Compared to the previous version, this new HILDA+ version 2.0 uses a base map from the year 2020 (based on ESA World Cover), integrates new remote sensing-based land cover datasets (see documentation sheet in the uploaded data), is calibrated on updated national land use statistics from FAO and includes additional cropland-related land use categories: tree crops, agroforestry and annual crops. See the documentation and the paper reference for the method of cropland mapping. Forests are subdivided into different forest types based ESA CCI Land Cover (1992-2020). HILDA+ version 2.0 covers the following land use/cover categories (given with their respective code numbers in the dataset): 11: Urban areas, 22: Annual crops, 23: Tree crops, 24: Agroforestry, 33: Pasture/rangeland, 40: Forest (unknown/other), 41: Forest (evergreen, needle leaf), 42: Forest (evergreen, broad leaf), 43: Forest (deciduous, needle leaf), 44: Forest (deciduous, broad leaf), 45: Forest (mixed), 55: Unmanaged grass/shrubland, 66: Sparse/no vegetation.